AUDIT ATAU PEMERIKSAAN ATAS PENGGUNAAN DANA BANTUAN OPERASIONAL PENDIDIKAN DAERAH (Studi Kasus pada SMK X Surabaya) - Ludviana, Intan Martinasari; Rustam, Akie Rusaktiva (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purposes of this research are: 1) determine the audit or examination that is used to report operational funding of education, 2) determine the procedures used to audit or examine operational support local education. This study used a qualitative research case study method. This study describes the object under study phenomenon the recapitulation sheet financial budget. Data obtained through the evidence and documentation. After that, the subject phenomenon analyzed to find the possibility of error and then provide advice. From the research that has been done can be concluded that: SMK X Surabaya not have adequate knowledge of accounting and auditing that are still experiencing an error at the time of engagement with the public accounting firm. We recommend using the default public accounting firm in accordance with the SPAP in conducting the audit. Keyword: accounting, auditing, engagement, examination